A new combination for a Chinese Zingiber (Zingiberaceae), Z. fallax. (28th March 2019) - Chen, Juan; Xia, Nian‐He; Bai, Lin
Abstract : Boesenbergia fallax Loes., previously known as a synonym of B. longiflora (Wall.) Kuntze, is recognized as belonging to the genus Zingiber Mill. Furthermore, it is conspecific with Z. liangshanense Z. Y. Zhu, which was incorrectly treated as a synonym of Z. striolatum in 'Flora of China'. A new combination, Z. fallax (Loes.) L. Bai, Juan Chen & N. H. Xia is proposed here, and Z. liangshanense is treated as its synonym. Lectotypes are designated for B. fallax and Z. liangshanense . Zingiber fallax is now known to occur in southern Sichuan Province and northwestern to central Yunnan Province, China.